Oscillatory mechanoluminescence of Mn2+-doped SrZnOS in dynamic response to rapid compression - Hao Wang; Tingting Zhao; Mei Li; Junlong Li; Ke Liu; Shang Peng; Xuqiang Liu; Bohao Zhao; Yanlong Chen; Jiao An; Xiaohui Chen; Sheng Jiang; et al. (Nature Communications)
Abstract Photon emission may be continuously produced from mechanical work through self-recoverable mechanoluminescence (ML). Significant progress has been made in high-performance ML materials in the past decades, but the rate-dependent ML kinetics remains poorly understood. Here, we have conducted systematic studies on the self-recoverable ML of Mn2+-doped SrZnOS (SrZnOS: Mn2+) under rapid compression up to ~10 GPa. Rate-dependent distinct kinetics is revealed: a diffuse-like ML behavior below ~1.2 GPa/s, oscillatory emission with a series of ML peaks at critical rate of ~1.2–1.5 GPa/s, and suppression of ML above 1.5 GPa/s. Analysis from the rate-independent structural evolution and photoluminescence under high pressures show that the oscillatory ML emission at the critical rate corresponds to multi-cyclic piezoelectrically-induced excitation (PIE) and self-recoverable processes. Both characteristic time (τ) for the PIE and self-recoverable processes are minimized at the critical rate, indicating the time limit of ML in the dynamic response to rapid compression. High temperature is slightly favorable for PIE, but is unfavorable for the self-recoverable process. The present work uncovers the temporal characteristics of self-recoverable ML and provides insight into understanding the rate-dependent ML kinetics in the mechanical-photon energy conversion, conducive to the design of ML-based optoelectronic devices.